PEMBELAJARAN BERBASIS KARAKTER DAN KONSELING PENINGKATAN DIRI UNTUK MENINGKATKAN PENDIDIKAN KARAKTER SISWA - Elis Yulianti; Mulfi Sandi Yuda; M Afrizal Maulana; Umban Adi Jaya; Rizki Chrisulianti (Jurnal Abdimas Bina Bangsa, 2024)
This counseling discusses the importance of character education and self-improvement in building a quality generation. Based on Constitution Number 20 of 2003 concerning the National Education System, education is carried out to create an optimal learning environment and activate students in developing various abilities, morals and personalities. The concept of character and self-improvement is influenced by the environment such as family, friends, and language. The character education strategy uses a Multiple Intelligence approach to optimize students' talents and character. Extension methods include a character-based learning approach, self-improvement counseling, and implementation case studies at SMPN 2 Cibadak. Counseling uses visual slides and interactive discussions, and pre- and post-surveys are carried out for evaluation. The results show an increase in participants' understanding and satisfaction with the materials and counseling methods, providing significant benefits for students at SMPN 2 Cibadak, Sukabumi Regency